Hybrid Catalytic Membranes: Tunable and Versatile Materials for Fine Chemistry Applications. (2016) - Gu, Yingying; Emin, Clélia; Remigy, Jean-Christophe; Favier, Isabelle; Gómez, Montserrat; Noble, Richard D.; Gin, Douglas L.; Macanás, Jorge; Domènech, Berta; Lahitte, Jean-François
Abstract: The aim of this work is the synthesis of polymer-stabilized Pd nanoparticles inside a functionalized polymeric porous membrane and to test them in metal-catalyzed organic reactions. A polymeric membrane support (Polyethersulfone) was functionalized with an ionogen polymer capable of retaining metallic nanoparticles (MNP) or MNP precursors using a UV photo-grafting method. Membranes were also obtained by casting sulfonated polyethersulfone (Cardo-type). The reactions were carried out by filtering solutions containing the reactants leading to full conversions within seconds. The amount of PdNP included in the materials and the catalytic activity were influenced by the properties of the grafted network.